Her stories : African American folktales, fairy tales, and true tales - Hamilton, Virginia; Dillon, Leo.; Dillon, Diane (New York : The Blue Sky Press, 1995)
Nineteen stories which focus on the magical lore and wondrous imaginings of African American women.
Her animal tales: Little girl and Buh Rabby -- Lena and Big One Tiger -- Marie and Redfish -- Miz Hattie gets some company -- Her fairy tales: Catskinella -- Good Blanche, bad Rose, and the talking eggs -- Mary Belle and the mermaid -- Mom Bett and the little ones a-glowing -- Her supernatural: Who you! -- Macie and Boo Hag -- Lonna and Cat Woman -- Malindy and Little Devil -- Her folkways and legends: Woman and man started even -- Luella and the tame parrot -- The mer-woman out of the sea -- Annie Christmas -- Her true tales: Millie Evans: plantation times -- Lettice Boyer: from way back -- Mary Lou Thornton: my family.
Includes bibliographical references (p. [111]-112)
880
460
Accelerated Reader AR
Keywords: African American women -- Folklore -- Juvenile literature